2015
DOI: 10.1590/1679-78251791
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and Elastic Stiffness of RHS "T" Joints: Part II - Combined Axial Brace and Chord Loading

Abstract: This paper deals with the behaviour of welded "T" joints between RHS sections submitted to tension brace loading combined with chord axial loading. In the companion paper (part I) a finite element model and a study without axial load in the chord, focusing on the joint behaviour as a function of the significant geometrical variables, were presented. In this part II paper, tension loading on the brace is incremented up to the joint failure, but is combined with different chord load levels in tension or compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…The cross-sections were represented by their mid-surfaces, accurately incorporating the actual component thicknesses. This modelling approach aligns with previous studies (Korol and Mirza [20], de Matos et al [21], [22]) which has demonstrated the capability of shell elements to offer precise solutions across a range of applications, effectively addressing transverse shear deformation considerations.…”
Section: Modelling In Abaqussupporting
confidence: 82%
“…The cross-sections were represented by their mid-surfaces, accurately incorporating the actual component thicknesses. This modelling approach aligns with previous studies (Korol and Mirza [20], de Matos et al [21], [22]) which has demonstrated the capability of shell elements to offer precise solutions across a range of applications, effectively addressing transverse shear deformation considerations.…”
Section: Modelling In Abaqussupporting
confidence: 82%